Development and testing of an integrated disease management package for multiple diseases of tomato - and K.K. MISHRA, K.K. PANDAY*, P.K. PANDAY (Indian Phytopathology, 2005)
Tomato crop is severely damaged by four diseases viz., damping off, bacterial blight, Alternaria blight and leaf curl. Integrated disease management (IDM) package was developed comprising of biological, cultural, physical and need based use of chemicals for targeting above four diseases. IDM package was tested for nursery pest management and main field problems after transplanting. One each of open pollinated variety and hybrid as well as two different cropping periods were considered for testing efficacy of IDM package. Detailed result of IDM module in experimental and farmer’s field along with chemical method and control is compared and discussed in detail in this paper.